Kemampuan Berpikir Kritis Siswa dengan Inkuiri Terbimbing dipadu Carousel Feedback pada Materi Sifat-sifat Cahaya di Sekolah Dasar - Muspratiwi Pertiwi MR; Lia Yuliati; Abd. Qohar (Graduate School of Universitas Negeri Malang, 2018)
The purpose of this study was to determine differences in critical thinking skills of students learning with guided inquiry learning model combined carousel feedback and student learning by inquiry learning model. This study is a quasi-experimental research design with posttest-only nonequivalent control group. The subjects were students of class as an experimental class Va and Vb grade students as a control group. Students in the experimental class was learned with model guided inquiry combined carousel feedback while students in the control class was learned with model guided inquiry. The instrument used to measure the success of this study is the essay to measure students' critical thinking skills. The results showed that the critical thinking skills of students in the experimental class and control class differ statistically through the achievements obtained by the difference T test critical thinking skills both classes, namely 0.029 <0.05. Thus, it can be said combined carousel guided inquiry learning feedback significantly affect the ability of students' critical thinking on the material properties of the light.Tujuan penelitian ini adalah untuk mengetahui perbedaan kemampuan berpikir kritis siswa yang belajar dengan model pembelajaran inkuiri terbimbing dipadu carousel feedback dan siswa yang belajar dengan model pembelajaran inkuiri. Penelitian ini merupakan penelitian eksperimen semu dengan desain posttest only nonequivalent control group. Subjek penelitian ini adalah siswa kelas VA sebagai kelas eksperimen dan siswa kelas VB sebagai kelas kontrol. Siswa pada kelas eksperimen dibelajarkan dengan model inkuiri terbimbing dipadu carousel feedback sedangkan siswa di kelas kontrol dibelajarkan dengan model inkuiri terbimbing. Instrumen yang digunakan untuk mengukur keberhasilan penelitian ini adalah soal esai untuk mengukur kemampuan berpikir kritis siswa. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis siswa pada kelas eksperimen dan kelas kontrol berbeda secara statistik melalui uji T diperoleh selisih capaian kemampuan berpikir kritis kedua kelas yaitu 0,029 < 0,05. Dengan demikian, dapat dikatakan pembelajaran inkuiri terbimbing dipadu carousel feedback berpengaruh secara signifikan terhadap kemampuan berpikir kritis siswa pada materi sifat-sifat cahaya.